PENGARUH METODE KOMANDO (TEKNIK AWALAN LOMPAT JAUH) TERHADAP HASIL LOMPAT JAUH GAYA JONGKOK PADA MAHASISWI KEPELATIHAN 2 A UNIVERSITAS RIAU - Sinaga, Nopa A; Agust, Kristi; ', Slamet (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The issue in this research is about the result of long jump squat style in 2 A Coaching Students University of Riau, that was still lacking. It can be seen while doing lecture athletic exercise in squat style long jump, there are many mistakes from the students such as lack in making a satisfying jump, which their jump length average is below 3 meters. Writer assumes it was because the prefilx rejected (sprint) not optimal so leap is not optimal, mean while he target of long jump length to be achieved is 4 meters. This research is an experimental research. The population in this research is 2A coaching students, University of Riau, and the sample in this research is all people in the population which are 8 people in total. The data collection technique is from pretest and posttest. The instrument that was used in this research is long jump, which aims to measure the results of long jump squat style . The independent variable is the command method (long jump start up technique) (X), the dependent variable is the result of long jump squat style (Y). After that, the data is processed statistically, to test the normality with Liliefors test at significance level 0,05α. The hypothesis is there is influence of the command method (long jump start up technique) on the results of long jump squat style. Based on the result of t test analysis , T result is 37,15 and T table is 18.12, it means T result > T table . It can be concluded that H a is accepted, it concludes that there is a significant effect on the command method (long jump start up technique) on the results of squat style long jump in 2A coaching students University of Riau.Key words: Command Method (Long Jump Start Up Technique), Long Jump Result,Squat Style Long Jump